(untitled) (Defense and Security Studies, 2023)
Nigeria from 2016 to 2023 has been facing new security challenges, including kidnapping of people for ransom, sporadic shooting of inhabitants, and the rustling of livestock. There is a rich history of how cities in Nigeria, erected defensive walls or fortifications to protect the inhabitants and their property against invaders, criminals, or rustlers centuries before the arrival of the European colonialists to Africa. The incessant attacks on rural communities, highways and urban centres have compelled criminologists and security experts to rethink and revisit the security strategies adopted in the past and worked effectively in protecting the populace and their belongings. Kingdoms and Empires, as well as Emirates in different parts of Africa, had developed or erected defensive walls or fortifications which if replicated in the 21st century, will ease neighbhourhood watch and community surveillance and policing. This paper has helped to identify cities in Nigeria with defensive walls and restrict entrances (gates) in places such as Kano, Katsina Sokoto, Zaria and Benin City. These are some of the cities known for prehistoric warfare and their people were brave and famous in intercity and inter-community battles. The study found that towns and cities in Nigeria and other parts of the world used defensive walls or fortified their jurisdiction against enemies or invaders. The strategy proved effective in protecting their people and property. Building defensive walls or fortifications of towns and cities that are facing acute security challenges in Nigeria can enable the Government and community members to protect the residents. The use of defensive walls will make the use of different mass surveillance tactics much easier because the areas are cordoned-off hence patrol, searching and arrest of criminals. Therefore, the researcher recommended that instead of spending huge amounts on the procurement of weapons by the Federal Government of Nigeria, the Government should erect or build fences that make criminal investigation more effective hence combat crime and criminals.